Towards Proergonomic Project Management- Initial Assumptions for the Application of Agent- Based Model in the Context of Project Success Factors - Wiktoria CZERNECKA (Communications of International Proceedings, 2020)
Projects are becoming an increasingly popular form of business activity in modern organizations. They allow for a structured approach to problem solving and thus increase the potential and competitiveness of the organization, as well as support the fulfillment of customers requirements. It is even intuitively assumed that the implementation of the project in the enterprise should be successful. With this in mind, criteria for project evaluation and methods of their analysis are sought. The same needs also occur in the case of projects with an ergonomic link, which, due to their specificity, can be assessed in many categories in relation to project management, but also implementation practice. This article presents a preliminary study of the applicability of agent-based modeling in assessing the success of a proergonomic project in the context of success factors identified on the basis of a literature review and expert recommendations. The process of selection of critical criteria for the project success was presented and the initial assumptions for the development of agents characteristics were indicated. Further directions of the model development and limitations of the conducted research were also listed.
Keywords: Project management; ergonomic project success criteria; agent- based modeling; proergonomic approach in project management.